New multichannel kinetic spectrophotometer-fluorimeter with pulsed measuring beam for photosynthesis research - Bína, David; Litvín, Radek; Vácha, Frantisek; Siffel, Pavel (Photosynthesis research, 2006)
A multichannel kinetic spectrophotometer-fluorimeter with pulsed measuring beam and differential optics has been constructed for measurements of light-induced absorbance and fluorescence yield changes in isolated chlorophyll-proteins, thylakoids and intact cells including algae and photosynthetic bacteria. The measuring beam, provided by a short (2 micros) pulse from a xenon flash lamp, is divided into a sample and reference channel by a broad band beam splitter. The spectrum in each channel is analyzed separately by a photodiode array. The use of flash measuring beam and differential detection yields high signal-to-noise ratio (noise level of 2 x 10(-4) in absorbance units per single flash) with negligible actinic effect. The instrument covers a spectral range between 300 and 1050 nm with a spectral resolution of 2.1, 6.4 or 12.8 nm dependent on the type of grating used. The optical design of the instrument enables measuring of the difference spectra during an actinic irradiation of samples with continuous light and/or saturation flashes. The time resolution of the spectrophotometer is limited by the length of Xe flash lamp pulses to 2 micros.
Keywords: časové faktory; kinetika; fluorometrie; Photosynthesis; Time Factors; Fluorometry; Spectrophotometry; Rhodobacter sphaeroides; Kinetics; spektrofotometrie; fotosyntéza